1996
DOI: 10.1021/jf9503568
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Changes during the Development and Ripening of the Fruit of Cucumis melo (Cv. Makdimon)

Abstract: Changes in the aroma volatiles, free amino acids, sugars, principal acids, and soluble minerals were studied during the development and ripening of the fruit of Cucumis melo L. Reticulatis group cv. Makdimon. Ethyl acetate was the most abundant volatile produced during the final growth stage, but ethanol was the major volatile found in immature fruit. Most of the free amino acids exhibited increases in concentration as the fruit underwent the ripening process. Sucrose, although absent in immature fruit, showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
54
1
6

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(69 citation statements)
references
References 28 publications
8
54
1
6
Order By: Relevance
“…Volatile compound concentration reached a maximum level at 43 d after anthesis, just before full slip (slip 0 separation) from the vine occurs with light pressure) (Wang et al 1996). Flavour volatile composition of the different melon types varies substantially, but appears to correlate with melon storage life.…”
Section: Influence Of Maturity On Volatilementioning
confidence: 99%
See 1 more Smart Citation
“…Volatile compound concentration reached a maximum level at 43 d after anthesis, just before full slip (slip 0 separation) from the vine occurs with light pressure) (Wang et al 1996). Flavour volatile composition of the different melon types varies substantially, but appears to correlate with melon storage life.…”
Section: Influence Of Maturity On Volatilementioning
confidence: 99%
“…Both fatty acid and amino acid biosynthesis are important to volatile formation in melons. The amino acids alanine, valine, leucine, and methionine increased during fruit ripening, in close association with volatile production and are believed to supply carbons for four groups of esters, ethyl acetate, 2-methylpropyl, 2-methylbutyl and thioether ester, respectively (Wyllie et al 1995;Wang et al 1996). When a comparison of amino acid content was made between the highly aromatic melon Makdimon and the low-aroma melon Alice, no significant difference in volatile concentration was found.…”
Section: Biosynthetic Pathways and Metabolismmentioning
confidence: 99%
“…Cell free extracts of 'Arava' were capable of acetylating a number of alcohols (1-butanol, 1-hexanol, 1-octanol, isoamyl alcohol, 1-octen-3-alcohol, benzyl alcohol, phenyl ethyl alcohol, and 3-methylthio-1-propanol), but it is probable that several AAT isoforms were present in the extract. On the other hand, Wang et al (1996) had shown that in another American cantaloupe genotype (Makdimon) the highest production of esters occurred during the latest stages of ripening.…”
Section: Estimation Of Aat Activity During Melon Ripening With Prefermentioning
confidence: 99%
“…For each sample, determinations were replicated three times. Sulphur was not analysed as its concentration is very low in melon tissues (Wang, Wyllie and Leach, 1996). The mineral content was estimated by subtracting the fraction of organic material (carbonjhydrogenjoxygenjnitrogen) per unit dry mass from one.…”
Section: Determination Of Elemental Composition and Calculation Of Comentioning
confidence: 99%